Total thyroidectomy versus hemithyroidectomy with intraoperative radiofrequency ablation for unilateral thyroid cancer with contralateral nodules: A propensity score matching study - Qianqian Yuan; Lewei Zheng; Jinxuan Hou; Rui Zhou; Gaoran Xu; Chengxin Li; Gaosong Wu (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background For unilateral papillary thyroid carcinoma (PTC) patients with contralateral benign nodules, optimal treatment decisions are made according to patient preference and the disease’s pathological features. This study was performed to evaluate the efficacy and complications of hemithyroidectomy with intraoperative radiofrequency ablation (RFA) compared with total thyroidectomy. Methods Patients with unilateral PTC and cytologically benign contralateral nodules were enrolled from 2014 to 2018. Total thyroidectomy or hemithyroidectomy with intraoperative RFA of the contralateral nodule was offered to patients who had anxiety regarding their disease. The operation-related parameters, transient or permanent nerve injury, hypocalcemia and disease recurrence, were recorded and compared between the two groups. Results After propensity score matching, 191 patients who underwent total thyroidectomy and 224 contralateral nodules in 191 patients underwent hemithyroidectomy with intraoperative RFA (HTRFA) were included. The volume reduction ratios of the contralateral nodules were 67.7% at 12 months and 95.8% at 24 months. The total thyroidectomy group reported significantly higher hypocalcemia than HTRFA within one year (7.8% vs. 2.6%, p = 0.022). Supplemental levothyroxine was not required in 28.3% (54/191) of the patients one year after HTRFA. With a median follow-up of 4.1 years, three recurrences (1.6%) were observed in the HTRFA, and no recurrence occurred in the total thyroidectomy group (p = 0.246). Conclusions Hemithyroidectomy for unilateral PTC and intraoperative RFA for contralateral nodules were acceptable and effective treatment approaches and did not increase the risk of complications. Graphical Abstract